Implementation of Scaffolding on Differentiated Learning English at Junior High School - Nur Fitriyani; Citra Prasiska Puspita Tohamba; Muflihun Muflihun (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The objective of this study as to investigate the implementation of scaffolding method in differentiated learning used by English teacher at SMP Negeri 9 Kendari. This study employed qualitative design which used observation and interview as instrument. The subject of this study was an English who has been teaching English for 5 years. The data of this study was analyzed by using Miles and Huberman (2014) qualitative data analyzed. The findings of this study showed that the English teacher has applied scaffolding process according to McKenzie’s theory (1999). The process was, scaffolding clear direction, scaffolding clarifies purpose, scaffolding keeps students on task, scaffolding offers assessment to clarify expectation, scaffolding points students to worthy sources, scaffolding reduces uncertainties, surprise, and disappointment, scaffolding delivers efficiency, and scaffolding creates momentum.